Aspectos socioambientais e a gestão da APA Estadual das Águas Vertentes - Daniella Eloi de Souza (2014)
The APAs are a category of protected area established in Brazil in 1981 and framed in 2000, in the group Sustainable Use in SNUC. The difficulty of APAs´managementpass by insufficient human and financial resources, as well as in other categories, but its particularfor their characteristics: the demand for sustainability, the great extent of these protected areas, the management of natural resources considered public be held in private territories and disagreementabout the aims of creating this category, as well as the blurring of the prohibitions to which that are submitted. This scenario worsens in APAs withouta management plan, where these issues tend to be implemented from the perception of the manager on the area. Thus, considering the absence of theManagement Plan to Águas Vertentess Protected Area- APAEAV, this research sought to conduct an exploratory study of the social and environmental aspects of the coveredarea and its management in order to contribute to the management of unit. The APAEAV was created in 1998, covers 76.310 located in part of seven municipalities in MG. This research was conducted using three approaches: the official point of view, that is the analysis of the unit management documents; the geographical point of view, that seeks to characterize the coverage area of the unit, from IBGE data and field studies; and the point of view of the residents, which analyzes the community perception of the area and the unit management, from the content analysis of interviews. Regarding the characterization of the area of APAEAV, 59 localities were spatialized. Residents of APAEAV are low-income, mostly belonging to the Eclass. They have a mosaic of activities that make up their income, but have noticed the state welfare programs as the basis of their family income. Four areas were identified in APAEAV with similar socio-environmental characteristics, which indicate the impracticability of executing the same plan of action for the entire unit, considering the peculiarities, different social and environmental demands for each area. The decreased amount of agricultural production and the strengthening of civil society are features that were raised as major changes in the region. The perception of residents regarding the APAEAV is still very early and very different in the territory, being furtherhow nearest surrounding the headquarters of the UC. About the management, the research shows that there are still prioritizing inspection and environmental education activities. It is understood that the extension staff are potential actions to achieve the proposed objectives, hardly implemented, such as management and development of economic activities. Finally, we see the need for a larger number of studies on the APAs, to identify convergent points in the management of these protected areas, seeking to lighten the official point of view "that came" these UCs and the practice their chances of management.